Critical Success Factors in the Fast food Industry: A Case of McDonald's - Kee, Daisy Mui Hung; Ho, Siew Ling; Ho, Yee Syuen; Lee, Tze Wey; Ma, HaoYu; Yin, Yuan (AIBPM Publisher, 2021)
The study is aimed to examine the critical success factors of McDonald's in the fast-food industry. As a leading global brand, McDonald’s has expanded operations into more than 100 countries such as Malaysia, China, and Japan. Its primary purpose is to be the customers' favorite eating place, focusing on customer experience. We employed the quantitative method. A total of 100 customers and 20 employees were surveyed. The result shows that innovation and technology strategies, job satisfaction, marketing strategies, and customer satisfaction are the critical factors that drive McDonald's success in the fast-food industry. The discussion and recommendations are presented.